Il était une fois la langue inclusive - Emily Lombardero (Glad!)
This paper is a stylistic study of feminine nouns in Marie-Catherine d’Aulnoy’s Contes, salient because rare (even coined by the author) and/or subject to a particular use in context. These nouns are examined first from a morphological and then semantic point of view, with particular attention paid to job titles and animal names ; thirdly, several figures of speech are explored that bring grammatical gender into play. In this study, we hope to create a dialogue between stylistic analysis and the history of language : the way D’Aulnoy stylizes the feminine gender, that we describe and interpret here, is indeed likely to interest contemporary deliberations about gender-inclusive language and, more broadly, linguistic representation of the sexes.